PENGARUH PENERAPAN E-MODULE IPS BERMUATAN PENDIDIKAN KARAKTER TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Didien Muhamad Ghafur, - (2023)
This research was conducted against the background of not yet applied EModulee social studies character-based in learning social studies on the material diversity in my country in elementary school. Character-based social studies EModulees can be used in overcoming the boredom felt by students in following the learning process in the classroom. Lack of enthusiasm and motivation of students in following the learning is a very central aspect of why character-based social studies E-Modulees can be used as media and student learning materials. The research method used in this study was Pre-experiment one group pretest-posttest. The research approach used is quantitative research with the help of SPSS 26. The research was conducted at SD N Sadu 01 Soreang District, Bandung Regency with the object of research 30 fifth grade students as samples. In class 4, data were collected using pre and post tests.. The results of the pretest obtained results with an average value of 57 and divided into very low, low, medium, high and very high categories. The results of the post test is the value with an average of 78 with divided into categories of low, medium, high and very high. In the study, non-parametric tests were also carried out because one of the data was not normally distributed. The nonparametric test used the Wilcoxon test with an asymp sig (2-tailed) value of 0.000. These results become one of the evidence of the influence on the treatment given because if the significance value <0.05 then the hypothesis is accepted.